A hill tribe community advisory board in Northern Thailand: lessons learned one year on - Carlo Perrone; Nipaphan Kanthawang; Phaik Yeong Cheah (BMC, 2024)
Abstract Northern Thailand and its neighbouring regions are home to several minority ethnic groups known as hill tribes, each with their own language and customs. Hill tribe communities live mostly in remote agricultural communities, face barriers in accessing health, and have a lower socio-economic status compared to the main Thai ethnic group. Due to their increased risk of infectious diseases, they are often participants in our research projects. To make sure our work is in line with the interests of hill tribe communities and respects their beliefs and customs, we set up a hill tribe community advisory board. We consult the members before, during, and after our projects are carried out. This manuscript recounts how we set up the community advisory board and our reflections following one year of activities. Our experience strongly supports engaging with community advisory boards when working with minority ethnic groups in lower and middle-income settings. In particular, we found that over time, as researchers and members familiarise with one another and their respective environments, exchanges gain meaning and benefits increase, stressing the advantages of long-term collaborations over short or project-based ones.